Rolling member and rolling bearing
By forming a nitrided layer on the surface of the steel components of the rolling bearing, the amount of residual austenite and the dislocation density are controlled, solving the problem of dimensional changes at high temperatures, achieving high hardness and wear resistance of the rolling bearing, and ensuring the long-term stability of the rolling bearing.
Patent Information
- Application Number
- CN202480019730.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-22
- Filing Date
- 2024-01-29
- Publication Date
- 2025-10-21
AI Technical Summary
Existing rolling bearings experience dimensional changes due to the decomposition of retained austenite at high temperatures, which affects dimensional stability and wear resistance. In addition, existing technologies increase steel costs or reduce surface hardness.
Steel rolling components that have undergone quenching and tempering have a nitrided layer formed on their surface. The nitrogen concentration is above 0.20% by mass, the carbon concentration is above 0.70% by mass and below 1.5% by mass, the hardness is above 820Hv and below 1000Hv, the amount of retained austenite is below 20% by volume, and the dislocation density is high to limit the volume expansion caused by the decomposition of austenite.
It improves the dimensional stability and wear resistance of rolling components, resists temperature rise and surface damage, and ensures the long-term stability of rolling bearings.
Smart Images

Figure CN120826540A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a rolling member and a rolling bearing. Background Art
[0002] Rolling bearings used in machine tool spindles and other applications require high dimensional stability because they are directly related to the machining accuracy of the machine tools. The raceway members and rolling elements that make up the rolling bearings are made of quenched and tempered steel. This means that the metallurgical structure of the steel that makes up the raceway members and rolling elements contains retained austenite.
[0003] When the temperature of a rolling bearing rises during use, retained austenite decomposes. The resulting volume expansion of the retained austenite causes dimensional changes in the raceway and rolling elements. Furthermore, these dimensional changes can lead to creep, increased contact pressure due to a reduction in the clearance between the raceway and rolling elements, premature damage caused by this increased contact pressure, and abnormal noise and vibration.
[0004] Furthermore, the dimensional stability of rolling bearings is reduced not only by structural changes but also by wear and surface damage (contamination, flaking, etc.).
[0005] Japanese Patent Application Laid-Open No. 2001-099163 (Patent Document 1) describes a raceway ring of a rolling bearing, and Japanese Patent Application Laid-Open No. 2006-322017 (Patent Document 2) describes a rolling element of a rolling bearing.
[0006] Japanese Patent Application Publication No. 2004-232858 (Patent Document 3) describes a bearing ring for a rolling bearing. Japanese Patent Application Publication No. 2004-339575 (Patent Document 4) describes a bearing ring for a rolling bearing. The bearing ring described in Patent Document 4 has its surface hardness increased by shot peening.
[0007] Japanese Patent Application Publication No. 2017-088958 (Patent Document 5), Japanese Patent Application Publication No. 2022-073906 (Patent Document 6), and Japanese Patent Application Publication No. 2022-108242 (Patent Document 7) describe rolling elements. The rolling elements described in Patent Documents 5, 6, and 7 have molybdenum-based, vanadium-based, or chromium-molybdenum-vanadium-based nitrides precipitated on their surface. Japanese Patent Application Publication No. 2016-108616 (Patent Document 8) describes a raceway ring of a rolling bearing. The raceway ring of Patent Document 8 has silicon-manganese-based nitrides precipitated on its surface.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Laid-Open No. 2001-099163
[0011] Patent Document 2: Japanese Patent Application Laid-Open No. 2006-322017
[0012] Patent Document 3: Japanese Patent Application Laid-Open No. 2004-232858
[0013] Patent Document 4: Japanese Patent Application Laid-Open No. 2004-339575
[0014] Patent Document 5: Japanese Patent Application Laid-Open No. 2017-088958
[0015] Patent Document 6: Japanese Patent Application Laid-Open No. 2022-073906
[0016] Patent Document 7: Japanese Patent Application Laid-Open No. 2022-108242
[0017] Patent Document 8: Japanese Patent Application Laid-Open No. 2016-108616 Summary of the Invention
[0018] Technical problem to be solved by the invention
[0019] The raceway ring described in Patent Document 1 has a low surface hardness (less than 752 Hv), which may result in reduced dimensional stability due to wear or surface damage. The rolling element described in Patent Document 2 has a high amount of retained austenite (over 20% by volume), which may result in reduced dimensional stability due to the decomposition of the retained austenite during use.
[0020] The raceway ring described in Patent Document 3 exhibits a significant rate of dimensional change despite being held at a low temperature for a short period of time. The raceway ring described in Patent Document 4 requires a process other than heat treatment to increase surface hardness. The rolling elements described in Patent Documents 5, 6, and 7 require the addition of molybdenum or vanadium to the steel that constitutes the rolling element, which increases steel costs.
[0021] In rolling bearings for machine tools, ceramic balls made of, for example, silicon nitride are sometimes used as rolling elements. In the raceway ring of Patent Document 8, surface damage is more likely to occur when using these ceramic balls as rolling elements, as the surface energy of silicon manganese nitride is close to that of silicon nitride.
[0022] The present invention has been made in view of the above-mentioned problems in the conventional technology. More specifically, the present invention provides a rolling element having improved dimensional stability.
[0023] Technical solutions used to solve technical problems
[0024] The rolling element of the present invention has a surface and is made of quenched and tempered steel and has a nitrided layer formed on the surface. The nitrogen concentration of the surface is greater than 0.20 mass%. The carbon concentration of the surface is greater than 0.70 mass% and less than 1.5 mass%. The surface hardness is greater than 820 Hv and less than 1000 Hv. The amount of retained austenite on the surface is less than 20 volume%. The dislocation density of the retained austenite on the surface and the dislocation density of the martensite on the surface are respectively 2.0×10 14 m -2 Above and 1.3×10 15 m -2 above.
[0025] Effects of the Invention
[0026] According to the rolling member of the present invention, dimensional stability can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is a cross-sectional view of the rolling bearing 100 .
[0028] Figure 2 It is a manufacturing process diagram of the rolling bearing 100. DETAILED DESCRIPTION
[0029] The embodiment of the present invention will be described with reference to the accompanying drawings. In the following drawings, the same or corresponding parts are marked with the same reference numerals, and repeated descriptions are omitted. The rolling bearing of the embodiment is referred to as rolling bearing 100.
[0030] (Structure of Rolling Bearing 100)
[0031] The structure of the rolling bearing 100 will be described below.
[0032] Rolling bearing 100 is, for example, a rolling bearing for a lathe. However, the use of rolling bearing 100 is not limited to this. Rolling bearing 100 can also be a rolling bearing for an electric vehicle axle. Furthermore, an electric vehicle axle is a three-axis structural unit consisting of, for example, a drive motor, a speed reducer, and an inverter. Rolling bearings for electric vehicle axles require not only dimensional stability but also foreign matter resistance and high load capacity.
[0033] Rolling bearing 100 may also be a rolling bearing for an electric brake. An electric brake is a unit composed of, for example, a motor, a reduction gear, a ball screw, a cylinder, and a control device. Rolling bearings for electric brakes require not only dimensional stability but also foreign matter resistance and high load capacity.
[0034] Rolling bearing 100 may also be used in an electric compressor. Electric compressors are used to cool the interior of a vehicle and to cool batteries and other onboard electronic devices, which can easily reach high temperatures. Rolling bearings for electric compressors require not only dimensional stability but also foreign matter resistance and high load capacity.
[0035] This embodiment can also be applied to mechanical parts other than rolling bearings. For example, it can be applied to gearboxes, electric actuators, positioning devices, electric jacks, servo cylinders, mechanical presses, electric servo presses, electric push rod steering gears, ball screws used in electric injection molding machines, gears, shafts and shafts of electric axles, and ball screws for electric brakes, etc. These mechanical parts require not only dimensional stability but also foreign body resistance and high load capacity. In addition, the ball screw is a mechanical part composed of a shaft, a nut (outer ring), a rolling element (ball) arranged between the track surface of the shaft and the track surface of the nut, a pipe, a ball return groove (Japanese: こま), an end cover, etc.
[0036] Figure 1 is a cross-sectional view of the rolling bearing 100. Figure 1 As shown, rolling bearing 100 includes an inner ring 10, an outer ring 20, a plurality of rolling elements 30, and a retainer 40. The central axis of inner ring 10 is referred to as central axis A. The direction of central axis A is referred to as the axial direction. The direction along the circumference of a circle centered on central axis A when viewed axially is referred to as the circumferential direction. The direction passing through and perpendicular to central axis A is referred to as the radial direction.
[0037] The inner ring 10 is annular and extends in the circumferential direction. It has a width surface 10a, a width surface 10b, an inner diameter surface 10c, and an outer diameter surface 10d. The width surfaces 10a and 10b are the axial end surfaces of the inner ring 10. The width surface 10a faces one side in the axial direction ( Figure 1 The width surface 10b is the opposite surface of the width surface 10b in the axial direction, and faces the other side in the axial direction ( Figure 1 on the left side of the ).
[0038] The inner diameter surface 10c and the outer diameter surface 10d extend circumferentially. The inner diameter surface 10c faces radially inward. The outer diameter surface 10d faces radially outward. In other words, the outer diameter surface 10d is radially opposite to the inner diameter surface 10c. One end and the other end of the inner diameter surface 10c in the axial direction are connected to the width surface 10a and the width surface 10b, respectively. One end and the other end of the outer diameter surface 10d in the axial direction are connected to the width surface 10a and the width surface 10b, respectively.
[0039] The inner ring 10 is fitted onto a shaft (not shown) at its inner diameter surface 10c. The outer diameter surface 10d has a raceway surface 10da. The raceway surface 10da contacts the rolling element 30. The raceway surface 10da extends circumferentially. The outer diameter surface 10d is recessed toward the inner diameter surface 10c at the raceway surface 10da. The raceway surface 10da is located axially at the center of the outer diameter surface 10d. The raceway surface 10da has a partial arc shape, for example, when viewed in a cross-section perpendicular to the circumferential direction.
[0040] The outer ring 20 is annular and extends in the circumferential direction. It has a width surface 20a, a width surface 20b, an inner diameter surface 20c, and an outer diameter surface 20d. The width surfaces 20a and 20b are the axial end surfaces of the outer ring 20. The width surface 20a faces one side in the axial direction ( Figure 1 The width surface 20b is the opposite surface of the width surface 20b in the axial direction, and faces the other side in the axial direction ( Figure 1 on the left side of the ).
[0041] The inner diameter surface 20c and the outer diameter surface 20d extend circumferentially. The inner diameter surface 20c faces radially inward. The outer diameter surface 20d faces radially outward. In other words, the outer diameter surface 20d is radially opposite to the inner diameter surface 20c. One end and the other end of the inner diameter surface 20c are connected to the width surface 20a and the width surface 20b, respectively, in the axial direction. The outer diameter surface 20d is connected to the width surface 20a and the width surface 20b, respectively, in the axial direction.
[0042] The outer ring 20 is fitted into the housing (not shown) at its outer diameter surface 20d. The inner diameter surface 20c has a raceway surface 20ca. The raceway surface 20ca contacts the rolling element 30. The raceway surface 20ca extends circumferentially. The inner diameter surface 20c is recessed toward the outer diameter surface 20d at the raceway surface 20ca. The raceway surface 20ca is located axially at the center of the inner diameter surface 20c. The raceway surface 20ca has a partial arc shape, for example, when viewed in a cross-section perpendicular to the circumferential direction. The outer ring 20 is positioned radially outward of the inner ring 10, with the raceway surface 20ca facing the raceway surface 10da in the radial direction.
[0043] The rolling elements 30 are spherical. They are positioned between the raceway surface 10da and the raceway surface 20ca. The rolling elements 30 have surfaces 30a. Surface 30a contacts the raceway surface 10da and the raceway surface 20ca. Multiple rolling elements 30 are arranged circumferentially. The retainer 40 is positioned between the outer diameter surface 10d and the inner diameter surface 20c. The retainer 40 retains the multiple rolling elements 30 so that the spacing between adjacent rolling elements 30 remains within a certain range.
[0044] The inner ring 10, outer ring 20, and rolling elements 30 are made of quenched and tempered steel. The steel forming the inner ring 10, outer ring 20, and rolling elements 30 preferably has the composition shown in Table 1. The composition range shown in Table 1 also includes SUJ2, a high-carbon chromium bearing steel specified in the JIS standard.
[0045] [Table 1]
[0046]
[0047] A nitrided layer 50 is formed on the surface of the inner ring 10, the surface of the outer ring 20, and the surface (surface 30a) of the rolling element 30. Nitrogen is dissolved in the steel in the nitrided layer 50. Furthermore, chromium nitrides are precipitated in the steel in the nitrided layer 50. The portion of the inner ring 10, outer ring 20, and rolling element 30 located farther from the surface than the nitrided layer 50 is referred to as the core 60. Specifically, the portion of the inner ring 10, outer ring 20, and rolling element 30 excluding the nitrided layer 50 constitutes the core 60. Nitrogen is not dissolved in the steel in the core 60, and no chromium nitrides are precipitated in the steel.
[0048] In the cross-sectional view perpendicular to the surfaces of the inner ring 10, the outer ring 20, and the rolling element 30, the nitrided layer 50 preferably has a thickness of 100 μm. 2 A total of five or more chromium nitrides having a grain size of 1.0 μm or less are present in the nitrided layer 50 , and the area ratio of the chromium nitrides in the nitrided layer 50 is 0.95% or more and 10% or less.
[0049] The area ratio of chromium nitrides was calculated by capturing a cross-sectional image of the nitrided layer 50 at 4000x magnification using a field emission scanning electron microscope (FE-SEM). This cross-sectional image was binarized and then processed to calculate the area ratio of chromium nitrides. Cross-sectional images of the nitrided layer 50 were acquired in three or more fields of view, and the area ratio was calculated as the average of these multiple cross-sectional images.
[0050] The particle size of each chromium nitride is obtained by obtaining the area of each chromium nitride using the same method as above, dividing the area by π, and multiplying the square root of the value by 2. 2 The number of chromium nitrides having a particle size of 1.0 μm or less in the cross-sectional image is calculated by counting the number of chromium nitrides having a particle size of 1.0 μm or less in the cross-sectional image determined by the same method as above and using the area of the cross-sectional image.
[0051] The nitrogen concentration on the surfaces of the inner ring 10, outer ring 20, and rolling element 30 is 0.20 mass% or higher. The nitrogen concentration on the surfaces of the inner ring 10, outer ring 20, and rolling element 30 can be 0.30 mass% or higher. The carbon concentration on the surfaces of the inner ring 10, outer ring 20, and rolling element 30 is 0.70 mass% or higher and 1.5 mass% or lower. The carbon concentration on the surfaces of the inner ring 10, outer ring 20, and rolling element 30 can be 0.70 mass% or higher and 0.95 mass% or lower. The above nitrogen concentrations were measured using an EPMA (Electron Probe Micro Analyzer).
[0052] The hardness of the inner ring 10, outer ring 20, and rolling element 30 surfaces is between 820 Hv and 1000 Hv. The hardness of the inner ring 10, outer ring 20, and rolling element 30 surfaces is measured using the Vickers hardness test method specified in the JIS standard (JIS Z 2244:2009). The hardness measurement is performed with a load of 300 g, and the average hardness value measured at three or more points is calculated.
[0053] If measuring the hardness of the inner ring 10, outer ring 20, and rolling element 30 surfaces is difficult, the hardness can be measured at a depth of 50 μm from the surfaces of the inner ring 10, outer ring 20, and rolling element 30. The hardness measured in this manner is also between 820 Hv and 1000 Hv.
[0054] The amount of retained austenite on the surface of the inner ring 10, the surface of the outer ring 20, and the surface of the rolling element 30 is less than 20 volume%. The amount of retained austenite in the core is, for example, greater than 0.1 volume% and less than 9 volume%. In addition, the above-mentioned retained austenite amount can be measured using X-ray diffraction. In this case, a chromium tube ball X-ray diffraction device is used. In the chromium tube ball X-ray diffraction device, the wavelength of the Cr-Kα ray is 2.29093×10 -10 m, tube voltage 30 kV, tube current 10 mA, collimator size 2 mm x 2 mm. When measuring the amount of retained austenite in the core 60, the test piece is preferably electropolished to prevent the retained austenite from undergoing work-induced transformation.
[0055] The dislocation density of retained austenite on the surface of the inner ring 10, the surface of the outer ring 20 and the surface of the rolling element 30 is 2.0×10 14 m -2 The dislocation density of the retained austenite on the surface of the inner ring 10, the surface of the outer ring 20 and the rolling element 30 is 1.3×10 15 m -2 The dislocation density of the retained austenite in the inner ring 10, the outer ring 20 and the core 60 of the rolling element 30 is preferably 4.5×10 14 m-2 above.
[0056] The dislocation density of retained austenite and the dislocation density of martensite were measured using a cobalt tube-sphere X-ray diffractometer. More specifically, the X-ray profiles of austenite and martensite were measured using a cobalt (Co) tube-sphere X-ray diffractometer. In this case, the wavelength of the Co-Kα ray in the cobalt tube-sphere X-ray diffractometer is 1.7889×10 -10 m, tube voltage 40 kV, tube current 50 mA, collimator size 1 mm diameter. The X-ray profiles of austenite and martensite were measured within the range of 2θ of 30° to 135°.
[0057] Second, based on the Rietveld analysis, the half-value width of the peak of the X-ray profile of martensite and austenite obtained by X-ray diffraction is separated into crystallite size and strain. Third, by applying the separated crystallite size and strain to the Williamson-Hall formula, the dislocation density of martensite and the dislocation density of austenite are obtained. The Williamson-Hall formula is expressed as ρ = 14.4 × ε 2 / b 2 , where ρ is the dislocation density (unit: m -2 ), ε is the above strain, b is the Burgers vector length (b=0.25×10 -9 m).
[0058] In the X-ray profile of martensite obtained by X-ray diffraction, the peaks at the {110}, {200}, {211}, and {220} planes are measured. In the X-ray profile of austenite, the peaks at the {111}, {200}, {220}, {311}, and {222} planes are measured. The Rietveld analysis is performed to minimize the influence of the {200} plane of martensite and the {200} plane of austenite, which have different elastic moduli.
[0059] After being kept at 160°C for 2500 hours, the dimensional change rate of the inner ring 10, outer ring 20 and rolling element 30 is 40×10 -5 The dimensional change rate of the inner ring 10, outer ring 20 and rolling element 30 after being kept at 160°C for 2500 hours is preferably within 15×10 -5 The dimensional change rate is calculated by subtracting the dimensions of the inner ring 10 (outer ring 20, rolling elements 30) before holding from the dimensions of the inner ring 10 (outer ring 20, rolling elements 30) after holding, and dividing the value by the dimensions of the inner ring 10 (outer ring 20, rolling elements 30) before holding.
[0060] (Method of Manufacturing Rolling Bearing 100)
[0061] Next, a method for manufacturing the rolling bearing 100 will be described.
[0062] Figure 2 FIG is a manufacturing process diagram of the rolling bearing 100. Figure 2 As shown, the method for manufacturing the rolling bearing 100 includes a preparation step S1 , a nitriding step S2 , a quenching step S3 , a cooling step S4 , a tempering step S5 , a post-processing step S6 , and an assembly step S7 .
[0063] In the preparation step S1 , the workpiece is prepared. The workpiece for forming the inner ring 10 or the outer ring 20 is annular. The workpiece for forming the rolling element 30 is spherical. The workpiece is made of steel having the composition shown in Table 1.
[0064] In the nitriding step S2, the workpiece is nitrided. The nitriding treatment is performed by heating and holding the workpiece in an atmosphere containing a nitrogen source. The heating temperature and nitrogen concentration in the atmosphere in the nitriding step S2 are set so that no compound layer forms on the surface of the workpiece. The nitriding step S2 causes nitrogen to penetrate from the surface of the workpiece into the interior. As a result, nitrogen forms a solid solution in the surface layer of the workpiece, and chromium nitrides precipitate on the surface of the workpiece. The nitriding step S2 is performed so that, after the post-treatment step S6, nitrogen reaches a position further inward than the surface of the inner ring 10, outer ring 10, and rolling element 30. During the nitriding step S2, the composition of the atmosphere can be adjusted so that the carbon concentration in the surface layer of the workpiece is lower than the carbon concentration in the steel constituting the workpiece. This adjustment is preferably performed so that the carbon concentration at the surface of the workpiece after the post-treatment step S6 is between 0.70 mass% and 0.95 mass%. If the carbon concentration is lower than that of the base metal, the amount of undissolved carbides decreases, causing the chromium in the undissolved carbides to diffuse into the base metal, making it easier for chromium-based nitrides to precipitate.
[0065] In the quenching step S3, the workpiece is quenched. This quenching is performed by heating and maintaining the workpiece at a temperature above the Al transformation point of the steel constituting the workpiece, and then cooling it to a temperature below the Ms transformation point of the steel constituting the workpiece. The quenching step S3 generates martensite and retained austenite in the steel constituting the workpiece. Furthermore, after quenching step S3, the workpiece can be repeated by heating the workpiece again to above the Al transformation point. Repeating the quenching step S3 refines the grain size, enhancing the effectiveness of the cooling step S4.
[0066] In the cooling process S4, the processing object component is subjected to subzero treatment. In addition, in the cooling process S4, the processing object component can also be subjected to cryogenic treatment (Japanese: cryo treatment) (super subzero treatment). In the subzero treatment, the processing object component is cooled to a temperature higher than -100°C and below room temperature. In the cryogenic treatment, the processing object component is cooled to a temperature below -100°C. By performing the cooling process S4, a portion of the retained austenite in the steel constituting the processing object component is transformed into martensite. In addition, before performing the cooling process S4, a low-temperature tempering process or a cleaning process can also be performed to prevent cracks.
[0067] In the tempering step S5, the workpiece is tempered. This is achieved by heating the workpiece to a temperature below the Al transformation point of the steel constituting the workpiece. More specifically, the workpiece is tempered to approximately 180°C. In the post-processing step S6, the surface of the workpiece undergoes mechanical processing such as grinding and lapping. Through these steps, the inner ring 10, outer ring 20, and rolling elements 30 are manufactured.
[0068] Furthermore, when the workpiece is heated at a temperature of 180°C or higher in the tempering step S5, the higher the heating temperature, the lower the dislocation density of the martensite, and the lower the hardness. On the other hand, if the cooling step S4 is performed, the dislocation density of the martensite is less likely to be reduced by the heating in the tempering step S5. Therefore, although the hardness decreases with increasing the heating temperature, a higher hardness than usual can still be achieved.
[0069] In the assembly step S7 , the inner ring 10 , the outer ring 20 , the rolling elements 30 , and the cage 40 are assembled together. The rolling bearing 100 is manufactured through the above steps.
[0070] In the above description, the case where the nitriding layer 50 is formed on all surfaces of the inner ring 10 surface, the outer ring 20 surface and the rolling element 30 surface is used as an example, but it only needs to be formed on at least one surface among the inner ring 10 surface, the outer ring 20 surface and the rolling element 30 surface.
[0071] (Effect of rolling bearing 100)
[0072] Next, the effects of the rolling bearing 100 will be described.
[0073] As a countermeasure to suppress the dimensional changes over time in quenched and tempered steel raceways or rolling elements, one approach is to reduce the amount of retained austenite by tempering at high temperatures. However, while high-temperature tempering can suppress the dimensional changes over time caused by the reduction in retained austenite, it can also reduce the hardness of the steel on the raceway or rolling element surfaces. If the surface hardness of the steel decreases, there is a risk of reduced surface damage resistance.
[0074] Subzero treatment or cryogenic treatment is performed on the inner ring 10, outer ring 20, and rolling elements 30 to reduce the amount of retained austenite in the steel. This subzero treatment or cryogenic treatment increases the dislocation density of the martensite in the steel, which in turn increases the dislocation density of the retained austenite in the steel. Consequently, the retained austenite in the steel constituting the inner ring 10, outer ring 20, and rolling elements 30 is surrounded by martensite with a high dislocation density. Even if the retained austenite in the steel decomposes due to the temperature increase associated with the use of the rolling bearing 100, the volume expansion caused by this decomposition is limited by the surrounding martensite with a high dislocation density, thus minimizing dimensional changes. Consequently, the inner ring 10, outer ring 20, and rolling elements 30 maintain dimensional stability against the temperature increases associated with use.
[0075] The inner ring 10, outer ring 20, and rolling element 30 are not tempered at high temperatures, resulting in slow decomposition of martensite on their surfaces. Furthermore, the nitrogen concentration on the surfaces of the inner ring 10, outer ring 20, and rolling element 30 is at least 0.2 mass%, and their surface hardness is increased through solid solution strengthening. As a result, the steel hardness on the surfaces of the inner ring 10, outer ring 20, and rolling element 30 is between 820 Hv and 1000 Hv. Consequently, the inner ring 10, outer ring 20, and rolling element 30 maintain dimensional stability, resisting surface damage and wear.
[0076] Furthermore, the surface of the rolling element 30 is sometimes subjected to high residual compressive stress during the pressurization process, making it less susceptible to indentation than the surface of the raceway rings (inner ring 10, outer ring 20). Therefore, even if only the raceway rings (inner ring 10, outer ring 20) are used as the rolling element in this embodiment, the surface damage resistance of the rolling bearing 100 can be improved.
[0077] (Evaluation of dimensional stability)
[0078] To evaluate dimensional stability, samples A to J were prepared. Samples A to J used SUJ2, a high-carbon chromium bearing steel specified in the JIS standard. As shown in Table 2, the surface and core properties of samples A to J varied.
[0079] [Table 2]
[0080]
[0081] Furthermore, by varying the ratio of gas components in the atmosphere during the nitriding step S2, the heating time, and the holding temperature, the nitrogen concentration on the surface of each sample and the precipitation state of chromium nitrides were adjusted. Furthermore, by varying the cooling temperature and holding time during the subzero or cryogenic treatment, the dislocation density of retained austenite on the surface, the dislocation density of martensite on the surface, the amount of retained austenite on the surface, and the dislocation density of retained austenite in the core 60 were adjusted for each sample.
[0082] Samples A and D-G underwent nitriding in step S2, followed by quenching in step S3. Furthermore, samples A, D-G were subsequently subjected to cryogenic treatment as cooling in step S4, followed by tempering at 180°C in step S5. For samples A, D-G, the surface texture was adjusted by adjusting the grinding allowance of the test pieces. Consequently, the amount of retained austenite and the dislocation density of the retained austenite in the core 60 were comparable for samples A, D-G, and G-G.
[0083] Samples B and C were subjected to the nitriding step S2 and then the quenching step S3. Furthermore, Samples B and C were subsequently subjected to cryogenic treatment as the cooling step S4, followed by tempering at 180°C in the tempering step S5. Furthermore, for Samples B and C, the amount of undissolved carbides was adjusted by adjusting the atmosphere concentration during the nitriding step S2.
[0084] Sample H underwent quenching step S3 under standard conditions, followed by cryogenic treatment as cooling step S4. Sample H was subsequently tempered at 180°C in tempering step S5. Sample I underwent quenching step S3 under standard conditions, followed by tempering at 180°C in tempering step S5. Sample J underwent nitriding step S2, followed by quenching step S3. Sample J was subsequently tempered at 180°C in tempering step S5.
[0085] <Abrasion resistance test>
[0086] In the wear resistance test, the shape of each sample was made into a block with a length of 20mm, a width of 10mm and a height of 5mm. In each sample, the surface of 20mm in length and 10mm in width was mirror-polished so that the arithmetic mean roughness was 0.005μm. In the wear resistance test, a rotating cylindrical member was pressed against the surface of each sample with a length of 20mm and a width of 10mm, and a load of 50N was applied. The dimensions of the cylindrical member were an outer diameter of 40mm, a width of 10mm and a small curvature of 60mm. The material of the cylindrical member was SUJ2, the surface hardness was 760Hv, and the arithmetic mean roughness of the surface was 0.01μm. The maximum contact surface pressure between the cylindrical member and each sample was 0.5GPa. Velocity Oil No. 3 (ISO VG2) manufactured by Mobil was used, and a felt pad was used to lubricate the cylindrical member and each sample.
[0087] The cylindrical member was rotated at a speed of 24.5 rpm for 60 minutes. After the cylindrical member was rotated for 60 minutes, the maximum depth of the wear scar on the sample surface was measured using a laser microscope to evaluate the wear resistance of each sample. The results of the wear resistance test are shown in Table 3.
[0088] [Table 3]
[0089]
[0090] As shown in Table 3, the wear depth of samples A to E and J was less than 0.8 μm, indicating good wear resistance. 2 The number of chromium nitrides with a particle size of 1.0 μm or less in the sample is 5 or more, and the area ratio of chromium nitrides is 0.95% or more. Samples H and J were cryogenically treated but not nitrided, so wear resistance was not improved. Furthermore, no specific relationship was found between the area ratio of undissolved carbides and wear resistance.
[0091] <Evaluation test of dimensional changes over time>
[0092] In the dimensional change evaluation test over time, each sample was shaped into a ring with an inner diameter of 54 mm, an outer diameter of 60 mm, and a width of 15 mm. Each sample was kept at a constant temperature of 160°C for 2500 hours, and the outer diameter change rate before and after this constant temperature holding was measured. The results of the dimensional change evaluation test over time are shown in Table 4.
[0093] [Table 4]
[0094]
[0095] As shown in Table 4, the dimensional change rate of samples A to H after being kept at a constant temperature of 160°C for 2500 hours was 40×10 -5 In particular, Sample A, Sample B, and Samples D to G showed high dislocation densities in martensite and retained austenite, and low dimensional change rates after constant temperature holding.
[0096] Condition A: The nitrogen concentration on the surface is 0.2 mass % or more. Condition B: The surface hardness is 820 Hv or more. Condition C: The retained austenite on the surface is less than 20 volume %. Condition C: The dislocation density of the martensite on the surface is 2.0×10 14 m -2 The above is recorded as condition D. The dislocation density of the surface martensite is set at 1.3×10 15 m -2 The above is recorded as condition E.
[0097] Samples A through E satisfy all of Conditions A through E. On the other hand, Samples F through J do not satisfy at least one of Conditions A through E. Samples A through E exhibit good wear resistance and dimensional change after constant temperature maintenance. On the other hand, Samples F through J exhibit poor wear resistance and dimensional change after constant temperature maintenance. This comparison experimentally demonstrates that satisfying Conditions A through E ensures dimensional stability due to wear and surface damage, as well as dimensional stability against temperature increases associated with use.
[0098] The embodiments of the present invention have been described above, but the above embodiments may be modified in various ways. In addition, the scope of the present invention is not limited to the above embodiments. The scope of the present invention is represented by the claims, and is intended to include all changes within the meaning and scope equivalent to the claims.
[0099] Explanation of symbols
[0100] 10 Inner ring, 10a, 10b width surfaces, 10c inner diameter surface, 10d outer diameter surface, 10da raceway surface, 20 Outer ring, 20a, 20b width surfaces, 20c inner diameter surface, 20ca raceway surface, 20d outer diameter surface, 30 Rolling element, 30a surface, 40 Cage, 50 Nitriding layer, 60 Core, 100 Rolling bearing, A Center shaft, S1 Preparation process, S2 Nitriding process, S3 Quenching process, S4 Cooling process, S5 Tempering process, S6 Post-treatment process, S7 Assembly process
Claims
1. A rolling element having a surface and made of quenched and tempered steel, wherein: A nitrided layer is formed on the surface. The nitrogen concentration on the surface is 0.20 mass % or more, The carbon concentration of the surface is 0.70 mass % or more and 1.5 mass % or less, The hardness of the surface is greater than 820Hv and less than 1000Hv, The amount of retained austenite on the surface is less than 20 volume %, The dislocation density of the retained austenite on the surface and the dislocation density of the martensite on the surface are 2.0×10 14 m -2 Above and 1.3×10 15 m -2 above.
2. The rolling member according to claim 1, wherein Chromium nitrides are precipitated in the nitrided layer. In the cross-sectional view perpendicular to the surface, the nitrided layer has a thickness of 100 μm. 2 A total of five or more chromium-based nitrides having a grain size of 1.0 μm or less are present in the nitrided layer, and an area ratio of the chromium-based nitrides in the nitrided layer is 0.95% or more and 10% or less.
3. The rolling member according to claim 1, wherein further comprising a core portion located further away from the surface than the nitrided layer, The dislocation density of the retained austenite in the core is 4.5×10 14 m -2 above.
4. The rolling member according to claim 2, wherein: further comprising a core portion located further away from the surface than the nitrided layer, The dislocation density of the retained austenite in the core is 4.5×10 14 m -2 above.
5. A rolling bearing comprising a track member and a rolling element arranged in contact with the track member. At least one of the track member and the rolling element is the rolling element according to any one of claims 1 to 4 .
Citation Information
Patent Citations
Rolling bearing
JP2001099163A
Rolling bearing and its manufacturing method
JP2004232858A
Method for producing parts of rolling device
JP2004339575A
Rolling bearing
JP2006322017A
Rolling bearing
JP2016108616A